1991
DOI: 10.1002/ajmg.1320380220
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric comparison of mentally retarded males with and without the fragile X syndrome

Abstract: An anthropometric survey of 41 variables (weight, height, 10 linear, 4 breadth, 22 craniofacial, 2 skinfold, and testicular volume), including multivariate discriminant analysis, was undertaken on 110 mentally retarded males (39 with and 71 without the fra(X) syndrome). The mean Z scores of the fra(X) syndrome males fell between −2.00 and 8.38 for bizygomatic diameter and testicular volume, respectively, and the range of the mean Z scores of the non-fra(X) males was from −2.64 to 2.26 for hand breadth and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 16 publications
(6 reference statements)
2
24
0
Order By: Relevance
“…A cytogenetic and clinical survey of 236 mentally retarded males (39 with and 197 without the fra(X) syndrome or other recognizable cause of their retardation) was undertaken recently including a comprehensive assessment of anthropometric variables, and significant differences were reported for 18 measurements (weight, height, 7 linear, 2 breadth, 5 craniofacial, 1 skinfold and testicular volume) (Butler et al 1991a, Butler & Singh 1993 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A cytogenetic and clinical survey of 236 mentally retarded males (39 with and 197 without the fra(X) syndrome or other recognizable cause of their retardation) was undertaken recently including a comprehensive assessment of anthropometric variables, and significant differences were reported for 18 measurements (weight, height, 7 linear, 2 breadth, 5 craniofacial, 1 skinfold and testicular volume) (Butler et al 1991a, Butler & Singh 1993 …”
Section: Methodsmentioning
confidence: 99%
“…Hagerman et al (1988) reported finding positive fragile X chromosome results in 50% of mentally retarded males who were examined and found to have large ears, macroorchidims, and hand callouses. Recently, Butler et al (1991aButler et al ( , 1991b and Hagerman et al (1991) reported that certain physical characteristics (e.g., ear width, testicular volume, bizygomatic diameter, head breadth, plantar crease, hyperflexibility) could be used to identify more than 90% of mentally retarded males with the fra(X) syndrome. Butler et al (1992) also reported anthropometric standards for clinical use for weight, height, head circumference, ear length and testicular volume for fra(X) syndrome males.…”
Section: Hhs Public Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…This study found a higher incidence of narrow inner canthal distance (100% v 88%). The narrow inner canthal distance associated with normal outer canthal distance is related to the long palpebral fissures observed in anthropometric studies 1,12 . Fifty percent of adult males have long ears and 30% prominent ears 8 .…”
Section: D D D Discussion Iscussion Iscussion Iscussion Iscussionmentioning
confidence: 90%